Teaching Indonesian Speaking Skills with A Gamification Approach - Yunarni Siregar; Ifan Iskandar; Ratna Dewanti (Universitas Syiah Kuala, 2022)
Speaking skills are essential language skills to master in the digital era. Indonesian teachers are therefore challenged to develop approaches and materials according to the development of students in this era. Gamification is an approach that Indonesian language teachers can develop to be more effective and make students involved in learning. This study intends to further explore gamification's effectiveness in learning speaking skills. The research is a quasi-experimental study involving 34 students of class XI IPS MAN 4 Jakarta in one learning session. All students were involved in total sampling and received treatment as a whole without a control group. The data were observed using a questionnaire according to the curriculum target and analyzed by frequency distribution. The results showed that gamification improved students' abilities, learning motivation, and engagement. The implication is that the gamification designed in this study can be further developed in accordance with the study's limitations. The game can also be developed digitally.